Low Dentin Matrix Protein 1 Is Associated With Incident Cardiovascular Events in Peritoneal Dialysis Patients. (7th September 2016) - Yoon, Chang‐Yun; Park, Jimin; Seo, Changhwan; Nam, Bo Young; Kim, Seonghun; Kee, Youn Kyung; Lee, Misol; Cha, Min‐Uk; Kim, Hyoungnae; Park, Seohyun; Yun, Hae‐Ryong; Jung, Su‐Young; et al.
ABSTRACT: Recent reports demonstrated that dentin matrix protein 1 (DMP1) acts as an inhibitor of vascular calcification and might be a potential biomarker for chronic kidney disease‐mineral and bone disorder; however, no clinical investigations regarding DMP1 have been performed in dialysis patients. We investigated the prognostic value of DMP1 on cardiovascular outcomes in prevalent peritoneal dialysis patients. We recruited 223 prevalent peritoneal dialysis patients and divided them into high and low DMP1 groups according to log‐transformed plasma DMP1 levels. Lateral lumbar spine radiographs were used for measurement of vascular calcification. Major cardiovascular events were compared between the two groups. A Cox proportional hazards analysis determined DMP1 was independently associated with cardiovascular outcomes. In vitro mouse osteocytes were cultured in media containing indoxyl sulfate (IS), and the expressions of DMP1 were examined. The mean age was 52.1 ± 11.8 years, and 116 (52.0%) patients were male. The median value of log DMP1 was 0.91 (0.32–2.81 ng/mL). The multiple logistic regression analysis indicated that DMP1 levels were independently associated with the presence of vascular calcification after adjustment for multiple confounding factors (odds ratio = 0.719; 95% confidence interval [CI] 0.522–0.989; p  = 0.043). During a mean follow‐up duration of 34.6 months, incident cardiovascular events were observed in 41 (18.4%) patients. A Kaplan‐Meier plot showed that the low DMP1 group had a significantly higher rate of incident cardiovascular events compared with the high DMP1 group (log‐rank test, p  = 0.026). In addition, multiple Cox analysis showed that low DMP1 was significantly associated with incident cardiovascular events (log 1 increase: hazard ratio = 0.855; 95% CI 0.743–0.984; p  = 0.029) after adjustment for multiple confounding factors. In IS‐stimulated osteocytes, mRNA and protein expression levels of DMP1 were significantly decreased compared with control osteocytes. We showed that low DMP1 levels were significantly associated with presence of vascular calcification and were independently associated with the incident cardiovascular events in prevalent peritoneal dialysis patients. DMP1 might be a potential factor contributing to cardiovascular complications in dialysis patients. © 2016 American Society for Bone and Mineral Research.